A multifaceted module of BRI1 ETHYLMETHANE SULFONATE SUPRESSOR1 (BES1)-MYB88 in growth and stress tolerance of apple. Issue 4 (13th January 2021) - Liu, Xiaofang; Zhao, Caide; Gao, Yuqi; Xu, Yao; Wang, Shujin; Li, Chaoshuo; Xie, Yinpeng; Chen, Pengxiang; Yang, Peizhi; Yuan, Li; Wang, Xiaofeng; Huang, Lili; et al.
Abstract: The R2R3 transcription factor MdMYB88 has previously been reported to function in biotic and abiotic stress responses. Here, we identify BRI1 ETHYLMETHANE SULFONATE SUPRESSOR1 (MdBES1), a vital component of brassinosteroid (BR) signaling in apple ( Malus  ×   domestica ) that directly binds to the MdMYB88 promoter, regulating the expression of MdMYB88 in a dynamic and multifaceted mode. MdBES1 positively regulated expression of MdMYB88 under cold stress and pathogen attack, but negatively regulated its expression under control and drought conditions. Consistently, MdBES1 was a positive regulator for cold tolerance and disease resistance in apple, but a negative regulator for drought tolerance. In addition, MdMYB88 participated in BR biosynthesis by directly regulating the BR biosynthetic genes DE ETIOLATED 2 ( MdDET2 ), DWARF 4 ( MdDWF4 ), and BRASSINOSTEROID 6 OXIDASE 2 ( MdBR6OX2 ). Applying exogenous BR partially rescued the erect leaf and dwarf phenotypes, as well as defects in stress tolerance in MdMYB88/124 RNAi plants. Moreover, knockdown of MdMYB88 in MdBES1 overexpression (OE) plants decreased resistance to a pathogen and C-REPEAT BINDING FACTOR1 expression, whereas overexpressing MdMYB88 in MdBES1 OE plants increased expression of SQUAMOSA PROMOTER BINDING PROTEIN-LIKE 3 （ MdSPL3 ） and BR biosynthetic genes, suggesting that MdMYB88 contributes to MdBES1 function during BR biosynthesis and the stress response. Taken together, our results reveal multifaceted regulation of MdBES1 on MdMYB88 in BR biosynthesis and stress tolerance. Abstract : A vital component of brassinosteroid (BR) signaling in apple directly regulates the expression of transcription factor gene in a dynamic and multifaceted mode, thereby influencing BR biosynthesis and stress tolerance.